IMPACT OF THE RUSSIA UKRAINE CONFLICT ON ECONOMIC DEGLOBALIZATION - Luthfi Wahyu Basuki (Universitas Nasional, 2023)
This study analyzes the implications of the Russian-Ukrainian conflict on economic deglobalization and trade relations between the United States and Russia. In the context of increasing trade barriers and economic sanctions, both countries face reduced trade, supply chain disruptions, and reduced investment. To reduce risks to economic growth, market diversification can be one solution. Geopolitical tensions in Ukraine have deglobalized the global economy driven by tensions in the economic relations between the United States and Russia. This can be seen in trade restrictions, supply chain disruptions, and investment. Furthermore, the two countries responded by diversifying their markets by seeking new trading partners, expanding trade networks, and developing alternative sectors in other regions such as Asia, North America, and Africa. The United States and Russia can also strengthen economic resistance and create new opportunities amidst conditions of global uncertainty